Cotton stalk fiber polylactic acid composite plastic and preparation method thereof
By combining degummed cotton stalk fiber powder with components such as polylactic acid and using specific additives, a cotton stalk fiber polylactic acid composite plastic with high toughness and heat resistance is solved, and the deformation of polylactic acid products under high temperature conditions and The problem of insufficient heat resistance achieves efficient degradation and environmental protection performance.
Patent Information
- Application Number
- CN202411611525.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
Existing polylactic acid products are prone to deformity under high temperature conditions, have poor flexibility, and are insufficient heat resistance, making them difficult to use in microwave heating or high temperature environments.
Using refined and degraded cotton stalk fiber polylactic acid composite plastic, by combining degummed cotton stalk fiber powder with polylactic acid and other components, chain extenders, tougheners, lubricants, nucleating agents, coupling agents and compatible Additives such as agents are extruded and granulated by a twin-screw extruder to prepare composite plastics with high toughness and heat resistance.
It significantly improves the toughness and heat resistance temperature of polylactic acid composite plastics, ensures that the products do not deform in high-temperature environments, reduces costs, and achieves rapid degradation in the natural environment, and reduces environmental pollution.
Smart Images

Figure CN119463435A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biodegradable materials, and specifically relates to a cotton stalk fiber polylactic acid composite plastic and a preparation method thereof. Background Art
[0002] In the process of cotton production, the main waste generated is cotton stalks, so the rational use of cotton stalks has become one of the hot topics of concern today.
[0003] In Xinjiang, my country, cotton is grown in a large area. It is an important economic crop and has abundant cotton stalk resources. The main components of cotton stalks include cellulose, lignin and pectin. Cotton stalk fiber is a new type of natural fiber. The research and application of cotton stalk fiber is actually the recycling of cotton by-product resources. Cotton stalks contain a large amount of cellulose, polypentose and other components. As an important renewable resource in agriculture, they have great prospects for development and utilization. At present, at home and abroad, the application methods of cotton stalks mainly include energy conversion, activated carbon, composite materials, carboxymethyl cellulose and other methods, and the cost of waste treatment is also relatively low.
[0004] Patent document CN106046836A discloses a cotton stalk plant fiber synthetic resin, comprising: 30-60 parts of cotton stalk powder, 5-10 parts of Sichuan wax, 15-40 parts of polycaprolactone, 3-8 parts of aliphatic polycarbonate, 15-40 parts of mung bean starch, 3-8 parts of pentaerythritol, 3-8 parts of gum arabic powder, 5-10 parts of ultrafine aluminum silicate, and 10-20 parts of polylactic acid fiber; its preparation process comprises the following steps:
[0005] (1) Grind cotton stalks to obtain fine cotton stalk powder; (2) Put pentaerythritol and aliphatic polycarbonate into a high-speed mixer, add Sichuan wax and stir evenly to obtain a primary mixed material; (3) Put cotton stalk powder into a high-speed mixer and mix with the primary mixed material, add mung bean starch and stir evenly, then cool to room temperature, and grind after solidifying into blocks to obtain cotton stalk fiber powder; (4) Put polycaprolactone and gum arabic powder into a reaction container and stir evenly, react at a temperature of 100°C to 160°C for 60 to 120 minutes, then add ultrafine aluminum silicate and cotton stalk fiber powder and continue to stir evenly, react at a temperature of 80°C to 120°C for 60 to 120 minutes, and grind after cooling to obtain a mixed additive material; (5) Put the mixed additive material and polylactic acid fiber into a high-speed mixer and stir evenly, then blend and extrude in a twin-screw extruder, and then injection mold to obtain a cotton stalk plant fiber synthetic resin. However, the document has the problem that the rigidity of the blended extrudate is insufficient, which will lead to incomplete molding of the cotton stalk plant fiber synthetic resin in the mold during the injection molding stage, resulting in injection molding bending and easy adhesion in the mold.
[0006] Patent document CN106009566A discloses a method for preparing a modified polylactic acid cellulose composite material, comprising the following steps: (1) preparing tough modified polylactic acid; (2) extracting nanocellulose microfibers from cotton stalk skin; (3) adding 70-85 parts of modified polylactic acid, 5-25 parts of nanocellulose microfibers, 1-3 parts of heat stabilizer, 0.5-1.5 parts of antioxidant, 1-3 parts of nucleating agent, and 2-4 parts of coupling agent; the nucleating agent is selected from at least one of modified ultrafine talc, substituted dibenzylidene sorbitol, and di(4-tert-butyl-benzoic acid) aluminum hydroxide, and the coupling agent is a silane coupling agent; vacuum drying and mixing according to a ratio so that the matrix moisture content of the dried blend is less than 50ppm, and then the blend is injection molded into a standard sample by a melt extrusion method. However, the document does not undergo acid leaching and organic acid pickling during the extraction of nanocellulose microfibers, and the short alkali boiling time has a relatively small degumming effect on cotton stalk bast fibers, resulting in insufficient removal of impurities such as hemicellulose; and the impure nanocellulose microfibers will result in insufficient heat resistance of the standard sample molded from the blend under high temperature conditions, which will lead to softening and low bending modulus in the standard sample molded under high temperature conditions. In contrast, the cotton stalk fiber powder added in the present invention can enhance the toughness of PLA, improve the problem of easy brittle cracking of polylactic acid composite plastics, enable polylactic acid composite plastics to have high toughness, significantly increase elongation at break and heat-resistant temperature, and greatly improve the heat-resistant temperature of polylactic acid composite plastics. Summary of the invention
[0007] The purpose of the present invention is to provide a refined and degradable cotton stalk fiber polylactic acid composite plastic and a preparation method thereof. The cotton stalk fiber polylactic acid composite plastic can solve the technical problem that existing daily life polylactic acid products are not suitable for use under high temperature conditions, such as high probability of product deformation and poor flexibility under microwave heating or in a high temperature use environment.
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0009] The cotton stalk fiber polylactic acid composite plastic of the present invention comprises the following components by mass fraction: 40% to 80% polylactic acid, 15% to 55% degummed cotton stalk fiber powder, 0.4% to 1% chain extender, 1% to 3% toughening agent, 1% to 3% lubricant, 0.3% to 1% nucleating agent, 0.3% to 1% coupling agent, and 0.3% to 1% compatibilizer;
[0010] The degummed cotton stalk fiber powder is obtained by processing cotton stalk bast through the steps of pretreatment, pickling, water washing, alkali boiling, fiber beating, pickling, drying and crushing, and has a particle size of 200-2000 meshes.
[0011] The degummed cotton stalk fiber powder is degummed cotton stalk fiber powder of different particle sizes obtained by pre-treating cotton stalk bast → drying → acid soaking → water washing → drying → primary alkali boiling → water washing → drying → fiber beating → secondary alkali boiling → water washing → drying → fiber beating → acid washing → water washing → drying → crushing → screening; for example, the degummed cotton stalk fiber powder is made from the cotton stalk bast of the Xinlu Zao No. 41 cotton variety bred by Xinjiang Fuxin New Science Seed Industry;
[0012] Wherein, the pretreatment is to boil the cotton stalk bast in boiling water at 95 to 105° C. for 50 to 100 minutes;
[0013] The pickling is carried out by using a H2SO4 solution with a concentration of 4 to 10 g / L, the soaking time is 40 to 80 min at a temperature of 50 to 65°C, and the bath ratio is 1:(20 to 50);
[0014] The water washing: first wash with hot water at 60-95°C, then wash with cold water at 5-20°C;
[0015] The alkali boiling comprises: using a sodium hydroxide or potassium hydroxide solution with a mass concentration of 6 to 15 g / L, adding sodium silicate accounting for 1% to 3% of the total mass of the alkali solution; soaking for 5 to 30 minutes at a temperature of 70 to 95° C., and a material-bath ratio of 1:(40 to 80);
[0016] The pickling is carried out by soaking in an oxalic acid solution with a concentration of 0.3 to 1.5 g / L at room temperature for 5 to 20 minutes.
[0017] Preferably, the chain extender is an epoxy resin copolymer containing 4 to 10 active epoxy groups in the molecule, such as BASF chain extender ADR 4468.
[0018] Preferably, the polylactic acid has a molecular weight of 80,000 to 100,000, a viscosity of 0.2 to 8 dL / g, and a density of 1.2 to 1.3 g / cm 3 Granular polylactic acid plastic; for example, Nature Works' 4032D grade product.
[0019] Preferably, the toughening agent is at least one of methyl methacrylate, gum arabic, maleic anhydride, xanthan gum and / or konjac gum.
[0020] Preferably, the lubricant is at least one of oleamide, paraffin, stearate and / or stearamide.
[0021] Preferably, the nucleating agent is at least one of an amide nucleating agent (for example, HPN-20E nucleating agent produced by Milliken & Company), a hydrazide nucleating agent (for example, dibenzoyl hydrazide sebacic acid, TMC-306 nucleating agent and TMC-300 nucleating agent produced by Shanxi Chemical Research Institute) and / or an inorganic nucleating agent (for example, layered silicate, phosphate, rare earth and / or ZnO nucleating agent).
[0022] Preferably, the coupling agent is at least one of a titanate coupling agent, a silane coupling agent and an epoxy resin coupling agent; preferably one or more of vinyl trimethoxy silane, vinyl triethoxy silane and / or γ-aminopropyl triethoxy silane.
[0023] Preferably, the compatibilizer is at least one of maleic anhydride grafted polylactic acid (MA-g-PLA), glycidyl methacrylate grafted polylactic acid (GMA-PLA) and / or maleic anhydride grafted polycaprolactone (MA-g-PCL).
[0024] The preparation method of a cotton stalk fiber polylactic acid composite plastic described in the present invention comprises the following steps: (1) stirring and mixing the polylactic acid, chain extender and compatibilizer to obtain a homogeneous mixture; stirring and mixing the degummed cotton stalk fiber powder and toughening agent to obtain powder 1; stirring and mixing the lubricant, nucleating agent and coupling agent to obtain powder 2; (2) feeding the homogeneous mixture, powder 1 and powder 2 into an extruder in proportion for extrusion granulation to obtain composite plastic particles.
[0025] Preferably, in the step of stirring and mixing the lubricant and the coupling agent, the stirring speed is 1500 to 2000 r / min and the stirring time is 30 to 50 min.
[0026] Preferably, the extruder is a twin-screw extruder.
[0027] Preferably, the extrusion temperature of the twin-screw extruder is set as: zone 1: 110°C, zone 2: 175°C, zone 3: 175°C, zone 4: 175°C, zone 5: 175°C, zone 6: 165°C, zone 7: 165°C, zone 8: 165°C, zone 9: 160°C, zone 10: 160°C, zone 11: 125°C, zone 12: 125°C, screen changer: 120°C, and die head: 170°C.
[0028] In the cotton stalk fiber polylactic acid composite plastic of the present application, the toughening agent can improve the tensile strength of polylactic acid at high temperature, and significantly increase the elongation at break and heat-resistant temperature of polylactic acid under high temperature conditions; the compatibilizer can improve the compatibility of the toughening agent and polylactic acid, and then promote the heat resistance of the composite plastic through the nucleating agent; the nucleating agent plays a heterogeneous nucleation role in the system, which can increase the crystallization rate, and refine the crystal size during the crystallization process to improve the heat resistance of the composite plastic; the coupling agent can promote the coupling of cotton stalk fiber powder and polylactic acid; the chain extender has good thermal stability and can promote the uniform dispersion of each component, so that the final composite plastic has excellent performance and excellent temperature resistance, which can significantly improve the low high temperature toughness problem of ordinary polylactic acid composite plastic. Compared with ordinary polylactic acid composite plastics, the polylactic acid composite plastic of the present application can not only retain the performance of polylactic acid during crystallization, but also can achieve high temperature resistance and toughening of polylactic acid without changing the rigid structure of polylactic acid, so that the polylactic acid composite plastic has excellent performance in all aspects.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] The degummed cotton stalk fiber powder of the present invention has a higher mechanical strength than other plant fibers. The addition of the degummed cotton stalk fiber powder can enhance the toughness of PLA, improve the problem that polylactic acid composite plastics are easy to be brittle, and enable the polylactic acid composite plastics to have high toughness, greatly improve the heat resistance temperature of the polylactic acid composite plastics, and ensure that the products are not deformed in a high-temperature use environment; in addition, the degummed cotton stalk fiber powder greatly reduces the cost, and the cotton stalk fiber and polylactic acid are easy to be rapidly decomposed in the natural environment by the enzymatic hydrolysis of microorganisms, the oxidation of air, the hydrolysis of rainwater, and the photolysis of the sun. The technical scheme of refining and decomposing in nature and being integrated into the soil to reduce the pollution to the natural environment enables the plastic degradable daily necessities made of the composite plastic to achieve the purpose of degradation, particle refinement, and reduction of environmental pollution in the natural environment after being discarded. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a photograph of the appearance of plastic particles made of the cotton stalk fiber polylactic acid composite plastic of the present invention.
[0032] Figure 2 The cotton stalk fiber polylactic acid composite plastic of the present invention is made into plastic particles, which are then injection molded into standard specimens, and then dried at 85° C. for 30 minutes and observed for appearance. DETAILED DESCRIPTION
[0033] Those skilled in the art should recognize that the present embodiment is only used to illustrate the present invention, and is not used to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.
[0034] The preparation process of the degummed cotton stalk fiber powder in Examples 1 to 6 of the present invention and Comparative Examples 1 to 2 is as follows:
[0035] The cotton stalk bast of Xinlu Zao 41 cotton variety bred by Xinjiang Fuxin New Science Seed Industry was pretreated → dried → acid soaked → washed → dried → first alkali boiled → washed → dried → fibered → second alkali boiled
[0036] → washing → drying → beating → acid washing → washing → drying → crushing → screening to obtain degummed cotton stalk fiber powder of different particle sizes; wherein:
[0037] (1) Pretreatment: Boil the cotton stalk bast in 100°C boiling water for 60 min.
[0038] (2) Acid soaking: Use H2SO4 solution with a concentration of 6 g / L, soak for 60 min at a temperature of 55°C, and the material-bath ratio is 1:30; the acid soaking treatment can directly remove part of the gum, lignin and hemicellulose in the bast of the cotton stalk, which has a good effect on the subsequent removal of pectin.
[0039] (3) Water washing: The several water washing steps in the preparation process are first washed with 75°C hot water and then with 10°C cold water. Too high water temperature may damage the fiber. The purpose of washing with hot water first is to prevent the detached lignin, hemicellulose and pectin from gathering together again and adhering to the fiber. It is difficult to wash it off, which may affect the residual glue rate of the fiber.
[0040] (4) Alkali boiling: Alkali boiling can remove most of the colloid in the bast of cotton stalks. The quality of the fiber and the degumming effect will be affected by the quality of alkali boiling. A NaOH solution with a mass concentration of 10 g / L is used, and sodium silicate accounting for 2% of the total mass of the alkali solution is added; the soaking time is 15 min at a temperature of 90°C, and the material-bath ratio is 1:50.
[0041] (5) Beating: The cotton stalk skin is repeatedly beaten along the longitudinal direction of the cotton stalk fiber to remove most of the colloid remaining on the fiber.
[0042] (6) Acid washing: Soak in 1 g / L oxalic acid solution at room temperature for 10 min. The use of oxalic acid solution can prevent the hydrolysis of cellulose during acid washing. Acid washing can not only neutralize the alkali solution attached to the cotton stalk bast fiber after alkali boiling, but also thoroughly wash away impurities such as colloid and hemicellulose remaining on the fiber, ensuring that the extracted cellulose has a high purity.
[0043] (7) After drying and crushing, the degummed cotton stalk fiber powder can be obtained by screening.
[0044] Embodiments 1 to 4
[0045] The raw material ratios of Examples 1 to 4 are listed in Table 1. Among them: polylactic acid is 4032D produced by Nature Works; the toughening agent is methyl methacrylate; the chain extender is BASF ADR 4468; the lubricant is stearate; the nucleating agent is HPN-20E polypropylene nucleating agent produced by Milliken; the coupling agent is vinyl trimethoxysilane; the compatibilizer is MA-g-PLA; and the particle size of the degummed cotton stalk fiber powder is 1200 meshes.
[0046] The preparation method of cotton stalk fiber polylactic acid composite plastic comprises the following steps: (1) stirring and mixing polylactic acid, a chain extender and a compatibilizer to obtain a homogeneous mixture; stirring and mixing cotton stalk fiber powder and a toughening agent to obtain a powder 1; stirring and mixing a lubricant, a nucleating agent and a coupling agent to obtain a powder 2; (2) feeding the homogeneous mixture, the powder 1 and the powder 2 into a twin-screw extruder in proportion for extrusion granulation to obtain composite plastic particles; the extrusion temperature of the twin-screw extruder is set as follows: zone 1: 110°C, zone 2: 175°C, zone 3: 175°C, zone 4: 175°C, zone 5: 175°C, zone 6: 165°C, zone 7: 165°C, zone 8: 165°C, zone 9: 160°C, zone 10: 160°C, zone 11: 125°C, zone 12: 125°C, screen changing: 120°C, die head: 170°C.
[0047] Table 1 Raw material formula of Examples 1 to 6 and Comparative Examples 1 to 2, unit: wt%
[0048]
[0049] Example 5
[0050] The raw material ratios of Example 5 are listed in Table 1. Among them: polylactic acid is 4032D produced by Nature Works; the toughening agent is maleic anhydride; the chain extender is BASF ADR 4468; the lubricant is stearate; the nucleating agent is TMC-306 nucleating agent; the coupling agent is vinyl triethoxysilane; the compatibilizer is GMA-PLA; and the particle size of the degummed cotton stalk fiber powder is 1000 mesh. The preparation method is the same as that of Example 1.
[0051] Example 6
[0052] The raw material ratios of Example 6 are listed in Table 1. Among them: polylactic acid is 4032D produced by Nature Works; the toughening agent is gum arabic; the chain extender is BASF ADR4468; the lubricant is stearate; the nucleating agent is sebacic acid dibenzoyl hydrazide and layered silicate in a mass ratio of 1:1; the coupling agent is γ-aminopropyl triethoxysilane; the compatibilizer is GMA-PLA; and the particle size of the degummed cotton stalk fiber powder is 500 mesh. The preparation method is the same as that of Example 1.
[0053] Comparative Example 1
[0054] The raw materials of Comparative Examples 1-2 are the same as those of Example 2, the proportions are listed in Table 1, and the preparation method is the same as that of Example 2.
[0055] Test experiment example
[0056] 1. The composite plastic particles of Examples 1 to 6 and Comparative Examples 1 to 2 were observed and measured. Figure 1 .
[0057] 2. The composite plastic particles of Examples 1 to 6 and Comparative Examples 1 to 2 were injection molded into standard strips by an injection molding machine. According to the provisions of GB / T1040.2, a universal tensile machine was used to test the tensile strength and elongation at break of the strips at a speed of 100 mm / min. The test results are shown in Table 2.
[0058] 3. The specimens of Examples 1 to 6 and Comparative Examples 1 to 2 were respectively placed in a hot deformation Vicat softening point testing machine to test heat resistance. According to the provisions of GB / T 1634.2-2019, the upper limit of displacement was set to 0.340 mm, the bending stress was 0.45 MPa, and the heat deformation temperature of Example 1 was tested. The test results are shown in Table 2.
[0059] Table 2 Test results of Examples 1 to 6 and Comparative Examples 1 to 2
[0060]
[0061]
[0062] As can be seen from Table 2, since no degummed cotton stalk fiber powder was added to Comparative Example 1, its elongation at break was significantly lower than that of other groups, indicating that the addition of degummed cotton stalk fiber powder can enhance the toughness of polylactic acid, improve the rigidity of polylactic acid composite plastics, and have no elongation problem. Since no degummed cotton stalk fiber powder was added to Comparative Example 1, its heat deformation temperature was the lowest; the degummed cotton stalk fiber powder content of Example 4 was low, and its heat deformation temperature was also low. The degummed cotton stalk fiber powder of Example 1 was the highest, and its heat deformation temperature was the highest, indicating that the addition of degummed cotton stalk fiber powder can enhance the heat resistance temperature of polylactic acid composite plastics. Since no chain extender was added to Comparative Example 2, the compatibility between polymers and polymers, polymers and substrates was poor, and the performance was poor, and its tensile strength was significantly lower than that of other groups.
[0063] The results show that with the increase in the proportion of degummed cotton stalk fiber powder, the elongation at break and heat resistance temperature of the degummed cotton stalk fiber polylactic acid composite plastic can be significantly increased under the premise of ensuring that the elongation at break, which is a rigidity index of the composite material, is qualified. This shows that the addition of degummed cotton stalk fiber powder can enhance the toughness of PLA, improve the problem of easy brittle cracking of polylactic acid composite plastic, make polylactic acid composite plastic have high toughness, greatly improve the heat resistance temperature of polylactic acid composite plastic, and ensure that the product does not deform in the high temperature use environment of the product. In addition, the preparation process of the technical solution of the present invention is green and pollution-free, and a large amount of natural plant fibers are used, and its carbon reduction can reach 35%-70%.
Claims
1. A cotton stalk fiber polylactic acid composite plastic, characterized in that: The invention comprises the following components by mass fraction: 40% to 80% of polylactic acid, 15% to 55% of degummed cotton stalk fiber powder, 0.4% to 1% of chain extender, 1% to 3% of toughening agent, 1% to 3% of lubricant, 0.3% to 1% of nucleating agent, 0.3% to 1% of coupling agent and 0.3% to 1% of compatibilizer; The degummed cotton stalk fiber powder is obtained by processing cotton stalk bast through the steps of pretreatment, pickling, water washing, alkali boiling, fiber beating, pickling, drying and crushing, and has a particle size of 200-2000 meshes.
2. The cotton stalk fiber polylactic acid composite plastic according to claim 1, characterized in that: The degummed cotton stalk fiber powder is prepared by pre-treating cotton stalk bast → drying → acid soaking → water washing → drying → primary alkali boiling → water washing → drying → fiber beating → secondary alkali boiling → water washing → drying → fiber beating → acid washing → water washing → drying → crushing → screening to obtain degummed cotton stalk fiber powder with different particle sizes.
3. The cotton stalk fiber polylactic acid composite plastic according to claim 2, characterized in that: The pretreatment is to boil the cotton stalk bast in boiling water at 95 to 105° C. for 50 to 100 minutes; The pickling is carried out by using a H2SO4 solution with a concentration of 4 to 10 g / L, the soaking time is 40 to 80 min at a temperature of 50 to 65°C, and the bath ratio is 1:(20 to 50); The water washing: first wash with hot water at 60-95°C, then wash with cold water at 5-20°C; The alkali boiling comprises: using a sodium hydroxide or potassium hydroxide solution with a mass concentration of 6 to 15 g / L, adding sodium silicate accounting for 1% to 3% of the total mass of the alkali solution; soaking for 5 to 30 minutes at a temperature of 70 to 95° C., and a material-bath ratio of 1:(40 to 80); The pickling is carried out by soaking in an oxalic acid solution with a concentration of 0.3 to 1.5 g / L at room temperature for 5 to 20 minutes.
4. The cotton stalk fiber polylactic acid composite plastic according to claim 1, characterized in that: The chain extender is an epoxy resin copolymer containing 4 to 10 active epoxy groups in the molecule.
5. The cotton stalk fiber polylactic acid composite plastic according to claim 1, characterized in that: The polylactic acid has a molecular weight of 80,000 to 100,000, a viscosity of 0.2 to 8 dL / g, and a density of 1.2 to 1.3 g / cm 3 Granular polylactic acid plastic.
6. The cotton stalk fiber polylactic acid composite plastic according to claim 1, characterized in that: The toughening agent is at least one of methyl methacrylate, gum arabic, maleic anhydride, xanthan gum and / or konjac gum; the lubricant is at least one of oleamide, paraffin, stearate and / or stearamide; the nucleating agent is at least one of amide nucleating agents, hydrazide nucleating agents and / or inorganic nucleating agents.
7. The cotton stalk fiber polylactic acid composite plastic according to claim 1, characterized in that: The coupling agent is at least one of a titanate coupling agent, a silane coupling agent and an epoxy resin coupling agent; the compatibilizer is at least one of maleic anhydride grafted polylactic acid, glycidyl methacrylate grafted polylactic acid and / or maleic anhydride grafted polycaprolactone.
8. The method for preparing cotton stalk fiber polylactic acid composite plastic according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) The polylactic acid, chain extender and compatibilizer are stirred and mixed to obtain a homogeneous mixture; the degummed cotton stalk fiber powder and toughening agent are stirred and mixed to obtain powder 1; the lubricant, nucleating agent and coupling agent are stirred and mixed to obtain powder 2; (2) The homogeneous mixture, powder 1 and powder 2 are fed into an extruder in proportion for extrusion granulation to obtain composite plastic particles.
9. The method for preparing cotton stalk fiber polylactic acid composite plastic according to claim 8, characterized in that: In the step of stirring and mixing the lubricant and the coupling agent, the stirring speed is 1500-2000 r / min and the stirring time is 30-50 min.
10. The method for preparing cotton stalk fiber polylactic acid composite plastic according to claim 8, characterized in that: The extruder is a twin-screw extruder; the extrusion temperature of the twin-screw extruder is set as follows: zone 1: 110°C, zone 2: 175°C, zone 3: 175°C, zone 4: 175°C, zone 5: 175°C, zone 6: 165°C, zone 7: 165°C, zone 8: 165°C, zone 9: 160°C, zone 10: 160°C, zone 11: 125°C, zone 12: 125°C, screen changer: 120°C, and die head: 170°C.
Citation Information
Patent Citations
Preparation method of modified PLA (polylactide) and cellulose composite
CN106009566A
Cotton stalk plant fiber synthetic resin and preparation process thereof
CN106046836A